Osteopathic clinical reasoning: An ethnographic study of perceptual diagnostic judgments, and metacognition. (June 2018) - McIntyre, Cindy; Lathlean, Judith; Esteves, Jorge E.
Abstract: Background: Clinical reasoning has been widely researched in the health sciences; however, in osteopathy it is still in its relative infancy. Objective: To explore the moment by moment clinical reasoning processes of an osteopath whilst with patients, to understand the role of perceptual diagnostic judgments, and metacognitive processes. Method: A qualitative interpretive study with a novel narrative method as an organising structure: the moment by moment thought processes of a single osteopath were recorded and transformed into descriptions of the interactions with patients. The descriptive texts were expanded into narratives using autoethnography and reflective practice. Narratives were then analysed using methods originating from grounded theory. Results: Our interpretations indicate that osteopaths establish a multisensory construct during clinical reasoning which enables both analytic and intuitive decision-making strategies. Clinical reasoning was monitored by a variety of metacognitive processes, including intuitive discernments such as feeling that a decision is correct, and the judgment that there is sufficient information to make that decision. Conclusions: This is the first study to explore the subjective moment by moment clinical reasoning and decision-making strategies of an osteopath whilst with patients. It suggests that perceptual diagnostic judgments are multisensory and include mental and visual imagery, and embodied senses. These enable analytic and intuitive diagnostic strategies that are accompanied by persistent metacognitive processes during the consultation, which guide the practitioner's decision strategies. Highlights: Strategies for improving momentary awareness could help osteopaths become more cognizant of their own clinical reasoning. Understanding perceptual diagnostic judgments and metacognition may guide education of clinical reasoning, and research. Understanding and improving metacognition could help prevent bias and error during clinical reasoning. A metacognitive framework for osteopathy may enhance clinical practice and pre-registration education.